Erosion Behaviour of HVOF Sprayed SiC-WC-Cr3C2 Multilayer Coating on 304 Stainless Steel. (2018) - Rao, K.V. Sreenivas; Girisha, K.G.; Jamuna, K.; Tejaswini, G.C.
Abstract: In the present work, solid particle erosion behaviour of High Velocity Oxy Fuel (HVOF) sprayed SiC-WC-Cr3 C2 multilayer coating on AISI 304 stainless steel was determined by Air Jet Erosion Test rig at room temperature. Ni/Cr powder was used as a bond coat between coating and substrate. Erosion experiments were conducted by using silica of average particle size 312µm for different time duration of 5, 10, 15 and 20 min. Vickers micro hardness test was carried out for both multi layer coated and uncoated samples to measure the hardness of the samples. Scanning Electron Microscope (SEM) was used to analyse the eroded surface of the samples. EDAX analysis confirmed the presence of W, Si, Cr and C in the coating. Erosion rate was determined by measuring the weight of the samples for both multilayer coated and uncoated samples before and after the test. SiC -WC-Cr3 C2 multilayer coated material shows better wear resistance than uncoated material.